Efeito imunomodulador dos esteroides ovarianos nas respostas inflamatórias local e sistêmica de vacas desafiadas com infusão intrauterina de lipopolissacarídeo - Magalhães, Layane Queiroz (2022)
In dairy cows postpartum, uterine infections promote a local and systemic inflammation and interfere in reproductive efficiency. Several systemic interactions generate a previous inflammatory response to the clinical signs of uterine diseases, which elevates some inflammatory factors, such as acute phase proteins and inflammatory cytokines. The aim of this study was to evaluate the effect of steroid hormones including progesterone (P4) and estradiol (E2) on systemic inflammatory response of cows challenged with an intrauterine infusion of lipopolysaccharide (LPS), and the response of estrogen receptor α (ESR1), progesterone receptor (PGR), interleukin 1β (IL1β), interleukin 6 (IL6), and chemokine ligand 5 (CCL5) gene expression in ovariectomized Gir cows exposed to these hormones. For this, four experimental groups were executed as: Group 1: control group (n = 8) – the cows did not receive hormonal administration before day +1; Group 2: 24h - E2 (n = 8) – the cows received E2 24 hours (day -1) before LPS challenge; Group 3: 24h - P4 (n = 8) – the cows received P4 24 hours (day -1) before LPS challenge; Group 4: 14d - P4 (n = 8) – the cows received P4 14 days (day -14) before LPS challenge. Four cows (n = 4) were challenged (day 0) with 20 mL of 0.9% NaCl + 12.5 mg/kg LPS, and four cows (n = 4) were challenged (day 0) with 20 mL of 0.9% NaCl. On day 0 and day +1 and day -14, clinical and female genital tract examination, blood sampling for hormonal dosage (P4 and E2) and endometrial samples for gene expression analyses (ESR1, PGR, IL1β and IL6) were performed. For hormonal dosage (P4 and E2), blood samples were collected on day -1. In the systemic response to LPS, an increase in haptoglobin (Hp) (control group; 24 h - P4 group; 14 d - P4 group) was observed, and on day +1 the Hp of 14 d - P4 group was higher when compared to the other groups. On day 0 in the 14 d - P4 group leukocytes and lymphocytes were higher when compared to control group (P < 0.01). On day +1 after LPS-challenge in the 14 d - P4 group a decrease in circulating lymphocytes, eosinophils, and monocytes (P < 0.05) was related. A neutrophilia with left shift in the two treatments with P4 (day +1), in addition to a thrombocytopenia and lower platelets compared to the 24 h - E2 group (P < 0.05) (day 0) were also recorded. A down regulation of PGR and ESR1 gene expression was verified when P4 was exposure for a long period; the exposure to E2 did not interfere with both PGR and ESR1 genes expression. Concentrations of P4 were capable to up-regulate the IL6 gene expression at 14d - P4 exposition, and when compared to the 24h - E2 exposition group, there was a significant difference in the expression of IL1β and IL6. The CCL5 gene expression was down-regulated only by the exposure to 24h - E2 It was concluded that ovariectomized Gir cows challenged with LPS, previously submitted to steroid hormones induce a systemic inflammatory response. Also, the systemic response is more intense after previous prolonged exposure to P4 and less intense after exposure to E2. Also, the concentrations of P4 and E2 regulate the ovarian steroid receptors (ESR1 and PGR) expression. Still, a long-term exposure to P4 up-regulated IL1β and IL6 gene expression while estradiol down-regulated CCL5 gene expression. This study provided an important information relating the effect of ovarian steroids on the systemic and local uterine inflammatory response of cows challenged with intrauterine LPS, after exposed to ovarian steroids hormones.